3D printed carbon based all-dielectric honeycomb metastructure for thin and broadband electromagnetic absorption. (June 2023) - Zhou, Qian; Qi, Chenxi; Shi, Tiantian; Li, Yuekun; Ren, Wei; Gu, Shengyue; Xue, Bei; Ye, Fang; Fan, Xiaomeng; Du, Lifei
Highlights: An 3D printed carbon based all-dielectric honeycomb metamaterial is proposed. A collaborative design with the dielectric and structural parameters is conducted. A relative bandwidth of 152.9% with a relative thickness of 0.107 is achieved. The multiscale loss mechanism for the designed honeycomb metamaterial is specified. Abstract: Excellent electromagnetic absorbers with comprehensive performances of thin thickness, lightweight, broadband and strong absorption have become a significant requirement for electromagnetic interference and stealth technologies. In this study, a honeycomb metamaterial absorber with the conductive coating is designed and proposed, with 3D printed honeycomb skeleton coated by the conductive coating composed of carbon fibers, carbon nanotubes and resin. The optimized metamaterial absorber realized > 90% absorption in 5.65 ∼ 40 GHz with a total thickness of 6 mm, indicating a relative bandwidth of 152.9% with a relative thickness of 0.107. The excellent performances of the proposed absorber were contributed by the synergy effect of the electric parameters of the fabricated composites as well as the geometry parameters of the honeycomb meta-structure, which induced multiple loss modes. The synergy design on the 3D printed honeycomb skeleton and conductive coating would give a new insight into designing lightweight ultra-broadband microwave metamaterial absorbers.